Extraction and derivatisation of active polysaccharides. (1st January 2019) - Liu, Yang; Huang, Gangliang
Abstract: Polysaccharide, as one of the main components of traditional Chinese medicine, has an important antioxidant effect, and its mechanism has been studied by more and more researchers. The preparation methods of Chinese traditional medicine polysaccharides and their derivatives were reviewed. In addition, the advantages and disadvantages of various preparation methods of different Chinese medicine polysaccharides and their derivatives were discussed.